Doubling throughput in urban roads by platooning*. Issue 3 (2016) - Lioris, Jennie; Pedarsani, Ramtin; Tascikaraoglu, Fatma Yildiz; Varaiya, Pravin
Abstract: Intersections are the bottlenecks of the urban road system because an intersection's capacity is only a fraction of the vehicle flows that the roads connecting to the intersection can carry. The saturation flow rate, and hence the capacity, can be doubled if vehicles can cross intersections in platoons rather than one by one as they do today. Platoon formation is enabled by connected vehicle technology. Doubling the saturation flow rate has dramatic mobility benefits: the throughput of the road system can be doubled without changing the signal control, or vehicle delay can be reduced by reducing the cycle time. These predictions draw on an analysis of a queuing model of a signalized network with fixed time control and they are validated in a simulation of a small urban network with 16 intersections and 73 links.